Glycerine levels for crossbred heifers growing in pasture: performance, feed intake, feed eficiency and digestibility - Farias, Mariana de Souza; Prado, Ivanor Nunes; Valero, Maribel Velandia; Zawadzki, Fernando; Silva, Robério Rodrigues; Eiras, Carlos Emanuel; Rivaroli, Dayane Cristina; Lima, Beatriz Silva (Semina: Ciências Agrárias, 2012)
This work was carried out to study the effect of levels different addition of glycerine on animal performance, feed efficiency and digestibility of heifers supplemented in Brachiaria brizantha cultivar Marandu pasture. The experimental period was 102 days. The first 14 days was the period of adaptation of heifers to experimental diets and management. It was used 36 crossbred heifers with an average initial weight of 226 + 12 kg and 13 months old. The heifers were distributed in a completely randomized design with four treatments and nine replicates: control = G00, G2.8 = 2.8%, G6.1 = 6.1% and G9.9 = 9.9% of glycerine in dry matter of diet. The heifers were weighed every 28 days for evaluation of average daily gain (ADG). The dry matter intake (DMI) was estimated from fecal output, recorded with the aid of chromic oxide (Cr2O3) as an external and indigestible dry matter (DMi) as marker internal. The total and partial apparent digestibility was estimated from fecal output determined by chromic oxide. The addition of glycerine in the diet caused a linear reduction (P < 0.05) in final weight (FLW) and average daily gain (ADG) of heifers. The daily intake of dry matter (kg/day) of supplementation, pasture and total was similar (P > 0.05) among treatments. The intake of ether extract increased linearly (P < 0.05) as there was an increase of glycerol in the diet. Carbohydrate intake decreased linearly (P < 0.05) depending on the levels of glycerine to diets. The inclusion of glycerine had no effect (P > 0.05) on the digestibility of dry matter, organic matter, neutral detergent fiber, crude protein, non-fibrous carbohydrates and carbohydrates total. Moreover, the inclusion of glycerine in the diets increased linearly (P < 0.05) the digestibility of ether extract. The inclusion of low-purity glycerine is not recommended because it provides a reduction in animal performance.